Opportunistic Fungal Infection Associated With COVID-19. (18th January 2021) - Cafardi, John; Haas, Douglas; Lamarre, Thomas; Feinberg, Judith
Abstract: We report 2 cases of severe coronavirus disease 2019 requiring prolonged hospitalization complicated by the late onset of opportunistic fungal infections, histoplasmosis, and cryptococcosis.